O uso de dentifrícios à base de pirofosfato no controle químico do biofilme, formação de cálculo dental e doenças periodontais: uma revisão integrativa - SOUZA, Ana Beatriz Carvalho de (2023)
Pyrophosphate-based toothpastes are available on the market because they are chemical compounds that act by inhibiting the formation and mineralization of dental calculus, as they bind to calcium ions present in saliva and bacterial plaque, helping to control and inhibit dental calculus. Therefore, dentifrices with pyrophosphate would have antiplaque properties, helping to reduce the amount of dental biofilm and, consequently, preventing the development of periodontal diseases. Objective : This monograph aimed to conduct an integrative literature review on the effect of kinds of toothpaste containing pyrophosphate in their composition regarding the chemical control of biofilm, dental calculus formation, and periodontal diseases. Methodology : Based on the PICOT strategy to define the guiding research question, electronic searches were conducted in the following databases: white literature: Medline (PubMed), Web of Science (WoS), LILACS, Embase, Scopus, and Cochrane; gray literature: Dans Easy, using Boolean operators and the following keywords: "toothpaste," "dentifrice," "pyrophosphate," "anti calculus," and "anti-tartar." There were no language or date restrictions for the search of manuscripts in any of the consulted databases. Results : 3,754 studies were found, of which 34 were selected for this review. All studies investigated the effects of pyrophosphate-based toothpaste on dental calculus indices, comparing before and after using these products. Based on the analyses performed, 25 studies indicated that the use of pyrophosphate-based toothpaste was able to reduce dental calculus formation. However, 4 studies observed that placebo toothpaste (without pyrophosphate) was more effective in inhibiting dental calculus. In comparison, 5 studies did not find a statistically significant difference in dental calculus indices between placebo toothpaste and pyrophosphate-based toothpaste. Conclusion : Based on the findings of this review, the use of pyrophosphate-based toothpaste has been shown to be effective in the chemical control of biofilm, inhibition of dental calculus formation, and consequently, in the prevention of periodontal diseases.